A study of the M235T variant of the angiotensinogen gene and hypertension in a sample population of Calabar and Uyo, Nigeria (2013)
A common molecular variant of the angiotensinogen gene had been reported to predispose some ethnic groups to hypertension. This case-control study was designed to determine the frequency and association of the angiotensinogen M235T al1ele with hypertension in residents of Calabar and Uyo cities, south-south Nigeria. The study involved 1308 subjects, 612 patients and 696 controls. The M235T variant was investigated using an allele specific polymerase chain reaction and enzymatic digestion to determine al1ele frequencies. Hypertensinogenic factors such as dietary habits, physical activity, smoking and drinking habits were assessed using questionnaires. Descriptive statistics, chi-square and multiple regression analysis were used to analyze the data obtained. The M235T al1ele frequency was high (0.94 for hypertensives and 0.96 for controls) though it was not associated with hypertension status. The odds ratio for hypertension was 0.64 (95% confidence interval: 0.39-1.06) there were no significant differences between the genotype frequency of hypertensives and controls. By multiple regression, hypertension was observed to be associated with age and was a predictor for systolic blood pressure in both patient r2 = 0.359; p < 0.05 and control groups r2 = 0.26.